Performance of Microfinance Providers; Does Social Efficiency matters? - Maeenuddin; Hamid, Shaari Abd; Nassir, Annuar MD; Ghayasuddin (The journal of contemporary issues in business and government, 2021)
Microfinance sector showed a tremendous growth for the last decade and got a considerable attention throughout the entire world specifically in the developing countries, but on the other side the number of poor people has not been decreased. The focus of this study is to investigate the social efficiency of microfinance providers and to examine the different factors or problems that affecting the social efficiency of microfinance providers. Social efficiency means to how efficientlytransfer the products and services of the MFPs to the society with minimum cost. Data Envelopment Analysis approach has been proposed for the measurement of social efficiency with the total assets, total number of staff, operational expenditure as input while Average loan balance/ borrower/GNIpc. Number of female borrowers and indicator of benefit to the poorest as output variables. Regression analysis is proposed to find out the impact of different factors on the social efficiency of microfinance providers. Factors affecting the social efficiency of microfinance providers includes the presence of aggressive marketing, focus on profit oriented programs, commercialization, high level of competition, entrepreneurial behaviors of the people, different cultural dimensions, high interest rates, political instability, growth addiction, focus on stability or short term profitability, focus on loan repayment, lack of follow-up programs, lack of awareness, miss use of loan, fear of defaults, lack of technical support etc. which have to be considered in future studies.